2007
DOI: 10.3997/1873-0604.2006031
|View full text |Cite
|
Sign up to set email alerts
|

3D resistivity imaging from an archaeological site in south‐western Anatolia, Turkey: a case study

Abstract: A large‐scale resistivity imaging survey was performed in the acropolis area of Archaic Cnidos, south‐western Turkey. This survey was a part of the geophysical studies conducted between 1999 and 2004. Two‐dimensional resistivity data were acquired along a number of parallel lines using a pole–pole array. The data was processed using a 3D inversion algorithm based on a robust technique. We also applied shaded‐relief processing to enhance the representation of the images of apparent‐resistivity data and inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Subsequent inversion processing of the observed apparent data then allows us to retrieve the true resistivity distribution of the underground that is useful to define the geometry and nature of subsurface targets, such as the soil/bedrock interface, strata thickness, or depth and width of anthropical structures. Although several wide-range ERT applications have been proposed (Drahor et al, 2007;Drahor et al, 2008;Papadopoulos et al, 2014), the ERT technique is generally used for the production of highly detailed pictures of specific features in smaller areas, to reduce the cost of the geophysical survey.…”
Section: Ert Surveymentioning
confidence: 99%
“…Subsequent inversion processing of the observed apparent data then allows us to retrieve the true resistivity distribution of the underground that is useful to define the geometry and nature of subsurface targets, such as the soil/bedrock interface, strata thickness, or depth and width of anthropical structures. Although several wide-range ERT applications have been proposed (Drahor et al, 2007;Drahor et al, 2008;Papadopoulos et al, 2014), the ERT technique is generally used for the production of highly detailed pictures of specific features in smaller areas, to reduce the cost of the geophysical survey.…”
Section: Ert Surveymentioning
confidence: 99%
“…This array provides a better description of lateral discontinuities, such as archaeological structures, than the Wenner array. However, it has also been demonstrated that the dipole–dipole array can be more affected by noise in stony areas than other symmetrical arrays; it produces relatively high anomaly effects but it often produces low signal‐to‐noise ratios in such areas (Drahor et al , ; Zhou and Dahlin, ). To overcome this problem, we used a time injection interval of 1 ms together with quality control adopting 0% for the standard deviation and five and eight as the minimum and maximum number of stacks.…”
Section: Geophysical Surveysmentioning
confidence: 99%
“…Di Fiore et al (2002) realised another tensor-invariant technique based on probability tomography measurements. Drahor et al (2007) carried out a full threedimensional electrical resistivity tomography.…”
Section: A11 Geoelectric Mappingmentioning
confidence: 99%